2019
DOI: 10.1108/ilt-08-2018-0320
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of misaligned water-lubricated polymer bearing with axial grooves

Abstract: Purpose The purpose of this paper is to analyze the lubrication behavior of misaligned water-lubricated polymer bearings with axial grooves. Design/methodology/approach A lubrication model considering journal misalignment, bush deformation and grooves is established. In dynamic analyses of shaft systems, bearings are usually simplified as supporting points. Thus, an approach for solving the equivalent supporting point location is presented. The influence of misalignment angle and groove number on film thickn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Cheqamahi et al (2016) established a computational fluid dynamics (CFD) model for a MGWJB with four axial grooves and found that adding grooves causes the increase of bearing eccentricity ratio and decrease of the rate of temperature rise. Lv et al (2019) investigated the lubricant film thickness and pressure of misaligned MGWJBs under different misalignment angles. With the finite element method, Zhao and Zhang (2020) investigated the influence of structure deformation on the lubrication performance of the eight-grooves water-lubricated journal bearing.…”
Section: Introductionmentioning
confidence: 99%
“…Cheqamahi et al (2016) established a computational fluid dynamics (CFD) model for a MGWJB with four axial grooves and found that adding grooves causes the increase of bearing eccentricity ratio and decrease of the rate of temperature rise. Lv et al (2019) investigated the lubricant film thickness and pressure of misaligned MGWJBs under different misalignment angles. With the finite element method, Zhao and Zhang (2020) investigated the influence of structure deformation on the lubrication performance of the eight-grooves water-lubricated journal bearing.…”
Section: Introductionmentioning
confidence: 99%